Physical exercise in the combined treatment for gynoid lipodystrophy: integrative literature review (Research, Society and Development, 2022)
The presence of gynoid lipodystrophy (LDG) in women, as an unsightly condition related to the skin and subcutaneous tissue, is a growing problem worldwide. A sedentary lifestyle is one of the most important factors in the formation of LDG, however, the investigation of effective and suitable methods for the control and treatment of cellulite is of great importance. This article aimed to make an integrative review of the literature on the results obtained through combined treatments for LDG, associated with physical exercise. From 34 studies evaluated in the Pubmed, SciELO and Google academic portals between 1990 and 2021, six were selected to analyze the methodology used in the studies, as well as the demographic data, study design, type of treatment, duration and frequency of treatment. treatment, the measures evaluated and the final results. The descriptors used were: physical exercise, cellulite, combined treatment. In view of the above, it became evident that all the therapies listed are effective in the treatment of LDG, whether in combination with physical exercise.